Physical activity, sports participation, and sustainable development in the Ibero-American region: a pilot implementation of indicators in Chile, Costa Rica, and Ecuador - Bauer, Robert; Sánchez-García, Raúl; Hernández, Daniela; Hernández-Angeles, Domingo F.; González, Silvia; Nieto, Inés; Mayo, Xián; Jiménez, Alfonso (Frontiers in Sports and Active Living, 2025)
BackgroundIn recognition of the potential contributions of sports and physical activity to national development and responding to international calls from organizations like UNESCO and the World Health Organization, a coalition of agencies and Ibero-American sports ministers endorsed the creation of an indicator set to assess the impact of sports participation and physical activity on sustainable development.MethodsThe Ibero-American Sports Council, UNESCO, and the German Agency for International Cooperation developed a set of twelve Sports and Development indicators and four key data points for the Ibero-American region. In 2024, the first national-level pilot implementation was completed in Chile, Costa Rica, and Ecuador, collecting data using specifically designed formulae.ResultsEach country was able to partially provide relevant data for the defined indicators, with Chile completing eight, Costa Rica four, and Ecuador seven indicators. All countries provided data for the key data points.ConclusionsThe first national pilot implementation of the proposed indicators—as part of its validation process—highlights the need for improved quality and accessibility of reliable data across the Ibero-American region. These indicators have the potential to assess, track, and compare policies related to physical activity and sports, and to identify challenges and opportunities for improvement.